Risky play in Icelandic preschools - Wilkinson, Rachel, 1982- (2015)
The purpose of this qualitative research was to determine whether the outdoor play areas in Icelandic preschools provide children with opportunities for risky play. Further to this the attitudes, perspectives and approaches that preschool teachers have towards risky play were explored. The final goal was to find out whether preschool teachers in Iceland encourage or hinder children´s risky play activities. It is hoped that this research will provide more information on the situation of risky play in Icelandic preschools and raise awareness to the importance of such play. Photographs were taken of six preschool play areas, three in an urban area and three in a rural area of North Iceland to assist during data analysis. Drawings of the photographs were included to assist the reader get a clearer picture of the play features. Semi-structured, one-on-one interviews, using open-ended questions, were chosen as the method to collect data from twelve preschool teachers. The results of this research show that overall play areas in Icelandic preschools offer some opportunities for risky play, especially climbing. However, these opportunities are limited due to the equipment only providing minimum risk and the preschool teachers’ perspectives and approaches to risky play. The research also found that the majority of preschool teachers in Iceland do not have a clear understanding of risky play, believing it is only climbing or rough and tumble play. Risky play in Icelandic preschools is, in many cases, controlled by the preschool teachers’ perception of risk. Many preschool teachers believe that changes are needed to ensure risky play is available in preschools. These changes include: more natural features in play areas and raising awareness among preschool staff and health and safety officials. A few preschool teachers expressed concern about strict rules regarding play features and felt that they no long had control over children’s play activities. Ritgerðin fjallar um hvort börnum í íslenskum leikskólum gefast tækifæri ...